Ovarian cellular fibromas: A cliniopathological and immunohistochemical analysis of 10 cases. - Basheska, Neli; Prodanova, Irina; Kubelka-Sabit, Katerina; Zografski, George (Springer, 2007)
BACKGROUND: Traditionally, cellular fibroblastic tumors of the ovary were classified as either cellular fibroma (CF) or fibrosarcoma. A recent study suggests that cellular fibromatous neoplasms with bland cytology and elevated mitotic counts are associated with favourable prognosis and should be diagnosed as "mitotically active cellular fibroma" (MACF) rather than fibrosarcoma. In addition to clinicopathological features, immunohistochemistry may aid in further differentiating between CF and MACF, but its role has not been analyzed so far. METHOD: We retrospectively analyzed the clinicopathological and immunohistochemical features of 10 cases of ovarian cellular fibroblastic tumors diagnosed either as CF or fibrosarcoma in the last seven years. Patient records and archival pathology specimens were reviewed and immunohistochemistry was performed using pan-cytokeratin, EMA, vimentin, inhibin-alpha, calretinin, CD10, CD99, alpha-smooth muscle actin (SMA), desmin, S-100, c-kit, estrogen (ER), progesterone receptor (PR), p53, bcl-2, and MIB-1 antibody. RESULTS: Utilizing criteria proposed by Irving et al. the tumors were reclassified as CF (0-3 MFs/10 HPFs, n=5) and MACF (>4 MFs/10 HPFs, n=5). The mean age of patients with CF and MACF was 44 and 36 years, respectively. All tumors were unilateral, and the mean tumor size of CFs was 6.0 cm and 13.3 cm for MACFs. The majority of the tumors were solid; four of them had a cystic component, while ovarian surface rupture was present in one CF and one MACF. All tumors consisted of cellular, intersecting bundles of spindle cells showing slight or moderate pleomorphism. The mean highest mitotic count was 2.3 MFs/10 HPFs for CF, and 7.6 MFs/10 HPFs for MACFs. Follow-up of 4 to 79 months (mean 38 months) was available in 9 patients and was uneventful in all cases. One patient with MACF died 15 days following the operation as a result of the intercurrent disease. Immunohistochemical analyses showed that spindle cells in majority of the tumors were immunoreactive for vimentin, alpha-SMA, inhibin-alpha, calretinin, PR, and bcl-2. All tumors were negative for pan-cytokeratin, EMA, CD10, CD99, c-kit, ER, and p53, while one CF was positive for S-100, and one MACF showed positivity for desmin. In addition, the MIB-1 labeling index (LI) in MACFs was higher (mean 14.4%, range 10-25%), than that in CF (mean 5.6%, range 3-10%). CONCLUSION: Our results confirm the immunophenotypic similarity between ovarian fibromas and cellular fibromatous neoplasms, and suggest that the use of MIB-1 LI may help in differentiating between CF and MAFC.
Keywords: ovary; cellular fibroma; mitotically active cellular fibroma; histology; immunihistochemistry; Ki-67; prognosis